READING NEWSPAPER FOR ENHANCING VOCABULARY - Ningsih, Ratih Ningsih; Syafitri, Dewi (Journal of English Education, Literature and Linguistics, 2023)
This research was conducted to increase vocabulary through reading newspapers and to determine the effectiveness of reading newspapers in increasing students vocabulary. This research uses library research method. This study also discusses reading comprehension, where reading comprehension can also improve vocabulary. Using the newspaper reading method to increase vocabulary in English class still makes it difficult for students to understand the meaning of the word. However, based on several previous studies, it can be concluded that reading newspapers can increase vocabulary and also significantly improve reading comprehension. Using this method can help teachers to be able to provide learning to students effectively, especially increasing vocabulary. In conclusion, reading English newspapers is very helpful for learning new words, idioms phrases and sentence structures. It also helps them to learn how to take out the meaning of the sentences. English newspapers help students to become better learners.